Implikasi Penanaman Nilai-Nilai Dasar Agama Islam terhadap Perilaku Anak di Taman Kanak-Kanak (TK) Al-Amien Jember: The Implications of Instilling the Fundamental Values of Islam on Children's Behavior at Al-Amien Kindergarten, Jember - St. Rodliyah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2007)
The current era of globalization has led to a decline in moral attitudes among children, including rising cases of depression and suicidal behavior, despite advances in intellectual development. This study aims to analyze the implications of instilling basic Islamic values on children's behavior at TK